The Discursive Underside of Psychoanalysis: Comments on Cooper's "Blurring Boundaries". Issue 2 (3rd March 2016) - Levin, Charles
Abstract : Surprising for a discipline so dependent on unverifiable reports and theoretical consensus building, psychoanalysis pays little formal attention to its own rhetoric and discourse. In Steven H. Cooper's thought-provoking challenge to the now highly conventionalized use of the term "boundary" in the mental health field, he raises important questions about the strategies of psychoanalytic theory. While placing Cooper's proposals in a historical context, this discussion of his paper explores the possibility that closer formal attention to our linguistic habits and the way we play games with words would benefit our capacity for creative clinical thinking.